Augmented Invariance Control for Impedance-controlled Robots with Safety Margins. Issue 1 (July 2017) - Jähne, Christoph; Hirche, Sandra
Abstract: Various robotic applications require enforcing constraints, to achieve task performance or to hinder the robot from causing danger. Especially in human-robot-interaction, collision avoidance and velocity limits are crucial for safety A promising approach to enforce adherence to safety margins is invariance control. Considering the system dynamics, it corrects a nominal control based on a switching policy. To overcome the resulting lack of smoothness in terms of control inputs and states, a control scheme is developed that adds dynamics to the input and thereby augments the system. In previous work it is shown that the closed loop system is stable in combination with an exponentially stabilizing nominal control. However, this could not be shown for impedance controlled robots. Therefore, in this paper, an augmented invariance control for robotic applications is developed and proven to be uniformly asymptotically stable with an impedance-type nominal control. The proposed control law is validated in experiments on a KUKA LWR4+ in a collision avoidance scenario demonstrating stable behaviour with improved smoothness and chattering characteristics while enforcing the imposed hard constraints.